Nickel-catalyzed formation of quaternary carbon centers using tertiary alkyl electrophiles - Xue, Weichao; Jia, Xiao; Wang, Xuan; Tao, Xianghua; Yin, Zhigang; Gong, Hegui (Chemical Society reviews, 2021)
Transformation of sterically hindered tertiary alkyl electrophiles under nickel-catalyzed conditions to forge C(sp 3 )-C bonds and simultaneously create challenging all-carbon quaternary centers has received growing attention in the recent years. The unique nature of nickel featuring flexible oxidation states ranging from Ni 0 to Ni IV , allows the effective activation of tertiary alkyl electrophiles through ionic (2e) or radical pathways. In nickel-catalyzed coupling of tertiary alkyl electrophiles, the competitive β-H elimination upon the resulting alkyl-Ni intermediate is relatively slow, thus benefiting the C-C bond forming process. Meanwhile, nickel-catalyzed radical addition of tertiary alkyl electrophiles to unsaturated C-C bonds has also advanced rapidly due to the successful incorporation of carboxylic acid and alcohol derivatives as radical precursors, and more importantly due to further interception of the intermediate radical adducts with nucleophiles and electrophiles to accomplish three-component cascade reactions. This review highlights these state-of-the-art nickel-catalyzed transformations of tertiary electrophiles, organized by reaction types with emphasis on the reaction mechanisms. This review provides a comprehensive summary of recent advances in nickel-catalyzed reactions employing tertiary alkyl electrophiles for the construction of quaternary carbon centers.